Medical training at UCLA: reflective critic of the medical discourse (Boletin Médico de Postgrado, 2020)
This study was conducted to develop a reflective critic about medical training in Venezuela in the 21st century, interpreting thoughts from the voices of expert doctors and young graduates from the Universidad Centroccidental Lisandro Alvarado (UCLA). This is a qualitative sociocritical study using critical hermeneutics and critical analysis of speech. Intentional sampling and interviewing was used to collect the narrative of the medical professionals. The results shows that medical training socializes the quantitative biomedical paradigm as the only valid option in the production of knowledge and in the academic world, with an evolutionist, organicist, rational and positivist approach, which divides the human being in parts. In Venezuela, a dual educational system exists: autonomous universities and the Bolivarian University with deep differences between them, which generate conflicting graduate profiles. Training of the future doctors implies developing medical knowledge, the know-how, learning how to be a professional and coexist with others. In conclusion, medical training must be performed in qualified and certified university centers; their graduates should have high scientific, technological and humanistic profiles which will allow them to provide pertinent and timely answers to the health problems of the Venezuelan population.
Keywords: higher education institutions; professional training; teaching; education; faculty, medical